Numerical Methods for Fluid Dynamics With Applications to Geophysics - Durran, Dale R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
This book is a major revision of Numerical Methods for Wave Equations in Geophysical Fluid Dynamics; the new title of the second edition conveys its broader scope. The second edition is designed to serve graduate students and researchers studying geophysical fluids, while also providing a non-discipline-specific introduction to numerical methods for the solution of time-dependent differential equations. The methods considered are those at the foundation of real-world atmospheric or ocean models, with the focus being on the essential mathematical properties of each method. The fundamental character of each scheme is examined in prototypical fluid-dynamical problems like tracer transport, chemically reacting flow, shallow-water waves, and waves in an internally stratified fluid. The book includes exercises and is well illustrated with figures linking theoretical analyses to results from actual computations. Changes from the first edition include new chapters, discussions and updates throughout. Dale Durran is Professor and Chair of Atmospheric Sciences and Adjunct Professor of Applied Mathematics at the University of Washington. Reviews from the First Edition: (3z(BThis book will no doubt become a standard within the atmospheric science community, but its comfortable applied mathematical style will also appeal to many interested in computing advective flows and waves. It is a contemporary and worthy addition to the still-sparse list of quality graduate-level references on the numerical solution of PDEs." SIAM Review, 2000, 42, 755-756 (by David Muraki) (3z(BThis book presents an extensive overview of past and current numerical methods used in the context of solving wave systems $1! = (BIt is directed primarily at flows that do not develop shocks and focuses on standard fluid problems including tracer transport, the shallow-water equations and the Euler equations $1! = (Bthe book is well organized and written and fills a long-standing void for collected material on numerical methods useful for studying geophysical flows." Bulletin of the American Meteorological Society, 2000, 81, 1080-1081 (by Robert Wilhelmson).s
Ordinary Differential Equations -- Finite-Difference Approximations for One-Dimensional Transport -- Beyond One-Dimensional Transport -- Conservation Laws and Finite-Volume Methods -- Series-Expansion Methods -- Semi-Lagrangian Methods -- Physically Insignificant Fast Waves -- Nonreflecting Boundary Conditions -- Numerical Miscellany.
Keywords: Mathematics; Geophysics; Numerical analysis; Mechanical engineering; Civil engineering; Mathematics; Numerical Analysis; Geophysics/Geodesy.; Mechanical Engineering; Civil Engineering; Electronic books